Phyllobaenus verticalis Say 1835 ... - Majka, Christopher G. (Zenodo, 2006)
Phyllobaenus verticalis (Say, 1835) NOVA SCOTIA: Kings Co.: Canard, 24.vii.1956 & 10.vii.1959, H.T. Stultz, (3), ACNS; Canard, 5.iii.1959, H.T. Stultz, emerged, ACNS; Coldbrook, 21.viii.1956, C.D. Dondale, ACNS; Nictaux, 8.vii.1946, H.T. Stultz, ACNS; Lunenburg Co.: Bridgewater, 30.vi.1965, B. Wright, (4), NSMC; Pictou Co.: Salt Springs, 16.vii.2002, C.G. Majka, along river, CGMC. PRINCE EDWARD ISLAND: Kings Co.: Woodville Mills, 30.vi.2003, C.G. Majka, shore of pond, (2), CGMC; Queens Co.: Millvale, 13.vii.2002, C.G. Majka, brackish marsh, CGMC. Newly recorded in Nova Scotia and Prince Edward Island. Scattered records from across the region except for Cape Breton Island (Figure 3). Several records from wet habitats. Knull (1951) records it on dead bittersweet (Celastrus scandens L.) (Celastraceae) infested with cerambycid larvae; grape (Vitis) (Vitaceae) infested with Phymatodes amoenus (Say) (Cerambycidae); birch (Betula) (Betulaceae ) infested with Agrilus betulae Fisher (Buprestidae); linden (Tilia) ... : Published as part of Majka, Christopher G., 2006, The checkered beetles (Coleoptera: Cleridae) of the Maritime Provinces of Canada, pp. 31-46 in Zootaxa 1385 on pages 36-37, DOI: 10.5281/zenodo.175098 ...